Analysis of Differences in Coper, Platinum and Iridium Spark Plugs on Fuel Consumption - Bahtiar Wilantara; Ismail Kholid; Hamid Nasrullah; Ulfa Nur Fitri Khoiriyah (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
The research aims to determine the effect of different spark plug variations on fuel consumption. The method used is a descriptive method. The tools and materials used are: copper spark plugs, platinum spark plugs, iridium spark plugs, 5 liter measuring cup, and pertalite. Fuel consumption analysis compared copper, platinum and iridium spark plugs with rpm 700, 1000, 1500, and 2000. Test results: 1) Fuel consumption for copper spark plugs with rpm 700, 1000, 1500, and 2000, namely 40ml, 10ml, 15ml and 10ml. 2) Fuel consumption for platinum spark plugs with rpm 700, 1000, 1500 and 2000, namely 20ml, 5ml, 25ml and 20ml. 3) Fuel consumption for iridium spark plugs with rpm 700, 1000, 1500 and 2000 is 50ml, 10ml, 10ml and 10ml. So platinum spark plugs are more fuel efficient than copper and iridium spark plugs.